Temperature dependent electronic band structure of wurtzite GaAs nanowires. Issue 3 (5th January 2018) - Vainorius, Neimantas; Kubitza, Simon; Lehmann, Sebastian; Samuelson, Lars; Dick, Kimberly A.; Pistol, Mats-Erik
Abstract : Temperature dependence of the indicated transitions in wurtzite GaAs. Abstract : It has recently become possible to grow GaAs in the wurtzite crystal phase. This ability allows interesting tests of band-structure theory. Wurtzite GaAs has two closely spaced direct conduction bands as well as three nondegenerate valence bands. The energies of the band edges are not well known, in particular not as a function of temperature. In order to improve the accuracy we have studied the temperature dependence of the conduction band minimum as well as of the second valence band maximum using resonant Raman scattering (of up to 3LO Raman lines). We find that the temperature dependence of the bandgap in wurtzite GaAs is very similar to that in zinc blende GaAs. Our results show that they have the same band gaps not only at 7 K but also at room temperature to within 5 meV. This is in some discrepancy with previous work. We find that the energy difference between the first two Γ9V and Γ7V valence bands is constant, around 100 meV, over the investigated temperature range, 7 K to 300 K. Due to a fortuitous spacing of the energy bands we find a very unexpected and strong quadruple resonance in the resonant Raman scattering.